1984
DOI: 10.1177/32.11.6491254
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy and X-ray microprobe analysis in detection of acetylcholinesterase in cultured embryonal carcinoma cells.

Abstract: Mouse F9 cells, induced by retinoic acid and dibutyryl cyclic adenosine rnonophosphate (cAMP) to differentiate into neural-type cells, were incubated for localization of specific acetylcholinesterase (AChE) activity according to the Karnovsky-Roots method where the final enzymatic reaction product is crystalline cupric ferrocyanide and Cuprous thiocholine iodide. By scanning electron microscopy (SEM) neural-type cells with long processes were seen. Most of these cells exhibited crystalline precipitates on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Only the latter take up the dye, and it was shown that cells containing iodine had altered ratios of electrolytes. Rechardt et al (1984) studied differentiating mouse cells by scanning electron microscopy and showed that acetylcholinesterase reaction product, containing iron and copper, could be detected only in those cells that had developed long processes and were evidently differentiating into neuraltype cells. Kirkham et al (1975) and Altman (1982, 1983) have described the application of XRMA to the problem of tracing neurons by injecting them with various ions, such as cobalt or nickel.…”
Section: Range Of Applications Of X-ray Microanalysis In Cytochemistrymentioning
confidence: 99%
“…Only the latter take up the dye, and it was shown that cells containing iodine had altered ratios of electrolytes. Rechardt et al (1984) studied differentiating mouse cells by scanning electron microscopy and showed that acetylcholinesterase reaction product, containing iron and copper, could be detected only in those cells that had developed long processes and were evidently differentiating into neuraltype cells. Kirkham et al (1975) and Altman (1982, 1983) have described the application of XRMA to the problem of tracing neurons by injecting them with various ions, such as cobalt or nickel.…”
Section: Range Of Applications Of X-ray Microanalysis In Cytochemistrymentioning
confidence: 99%